2013
DOI: 10.1037/a0033659
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of behavioral measures of impulsive choice, impulsive action, and inattention.

Abstract: Behavioral measures of impulsivity are widely used in substance abuse research, yet relatively little attention has been devoted to establishing their psychometric properties, especially their reliability over repeated administration. The current study examined the test-retest reliability of a battery of standardized behavioral impulsivity tasks, including measures of impulsive choice (delay discounting, probability discounting, and the Balloon Analogue Risk Task), impulsive action (the stop signal task, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
120
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(133 citation statements)
references
References 57 publications
13
120
0
Order By: Relevance
“…SST performance has been found to have a significant relationship to impulsivity (Logan et al 1997). SSRT test-retest reliability has been found to be r=0.65 (Weafer et al 2013). …”
Section: Behavioral Measurementioning
confidence: 96%
“…SST performance has been found to have a significant relationship to impulsivity (Logan et al 1997). SSRT test-retest reliability has been found to be r=0.65 (Weafer et al 2013). …”
Section: Behavioral Measurementioning
confidence: 96%
“…Previous research has shown that D measures represent a stable, trait-like characteristic. Across several studies, estimates of the test–retest reliability of DD measures ranged from .55 to .90 (Baker et al, 2003; Beck and Triplett, 2009; Johnson et al, 2007; Kirby, 2009; Ohmura et al, 2006; Simpson an Vuchinich, 2000; Smits et al, 2013; Weafer et al, 2013). However several aspects of these previous studies warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…A predrink or baseline measure of behaviour also provides a means for controlling for day-to-day fluctuations in behaviour. This is particularly important for the stop-signal task given its relatively low test-retest reliability in healthy individuals (Kuntsi et al, 2001;Weafer et al, 2013;Wöstmann et al, 2013;Hedge et al, 2017) i.e., intra-class correlation coefficients between 0.03 (Wöstmann et al, 2013) and 0.65 .…”
Section: Alcohol Effect On Manual Ssrt Is Smaller Than Previously Repmentioning
confidence: 99%